When motion becomes emotion : a study of emotion metaphors derived from motion verbs - Sandström, Karin (2006)
The work presented in this D-extended essay has been carried out as part of the project “Linguistics in the Midnight Sun” at the Department of Languages and Culture, Luleå University of Technology. The aim of this essay was to investigate into the use of verbs of motion in emotion metaphors. The sixteen verbs studied are: climb, crawl, dive, float, fly, go, hop, jump, leap, plunge, roll, run, stagger, swim, tiptoe and walk. Verbs of motion are used because they are essential for the construal of the emotion following the human tradition of expressing the abstract, the emotion, in terms of the concrete, the motion. Furthermore, verbs of motion are often used because the behavioural response to emotional impact is used as source domain for the metaphor. Climb, fly, go, hop, jump & run are used in metaphors for ANGER/FURY. Crawl, leap, run, stagger, tiptoe & walk are used in metaphors for FEAR. Float, jump, leap, roll & walk are used for JOY/HAPPINESS and go & walk are used for SADNESS. The connections with specific emotions seem to arise out of the semantic parameters of each verb. The majority of the emotion metaphors in this study express basic negative emotions such as ANGER and FEAR. The human mind uses concrete experience to express the abstract. The human being visualizes the emotion as being inside a person, as surrounding the person or as making the person perform a movement. In this study, the majority of the studied verbs visualize a movement associated with an emotion. Understanding a metaphor is an advanced cognitive process based on pre-understanding, ability for abstract thinking and ability for sorting out one single cognitive model of the verb knowing that each verb has several possibilities, obviously the human mind is able to perform a very advanced process within a fraction of a second. Validerat; 20101217 (root)